PENGARUH EDUKASI AUDIOVISUAL PENDEKAR TERHADAP POLA HIDUP KELOMPOK BERESIKO KANKER PAYUDARA - ladesvita, fiora; Santi Herlina; Rio Wirawan (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Background: Breast cancer ranks first in terms of the highest number of cancers in Indonesia and is one of the first contributors to death due to cancer. Globocan data for 2020, the number of new cases of breast cancer reached 68,858 cases (16.6%) out of a total of 396,914 new cases of cancer in Indonesia. One effort that can be made to prevent breast cancer is through health education in audio-visual-based digital form which has been proven to increase the knowledge of vulnerable community groups. Objective: The aim of this research is to analyze the influence of PENDEKAR education on the lifestyle of groups at risk of breast cancer. Method: This research is a quantitative research with a quasi-experimental design using a non-control group pre-posttest approach. The population in this study were all women in the Limo Health Center working area. The sampling technique in this research was purposive sampling, with inclusion criteria, female gender, over 18 years old, able to read and write, and willing to be a respondent. The sample calculation was carried out using the Lemeshow proportion estimation formula and a total sample of 54 respondents was obtained. The data collection instrument used was a questionnaire. Univariate analysis techniques and bivariate analysis with dependent t test. Results: The research results showed that the mean risky lifestyle before the intervention was 22.59 (SD = 4.007) and after the intervention was given, the mean risky lifestyle was 20.76 (SD = 3.791). From the results of statistical tests, it can be concluded that there is a difference between lifestyle patterns before and after being given the PENDEKAR educational intervention (p value = 0.001; α 0.05).